PENGARUH MODEL PEMBELAJARAN ROLE PLAYINGBERBANTUAN TEKS DIALOG TERHADAP KOMPETENSI KETERAMPILAN BERBICARA DALAM BAHASA INDONESIA - IA Made Widyari (Journal for Lesson and Learning Studies, 2018)
This study aims to know significant differences in the competence of speaking skill in Indonesian between groups of students who were taught by role playing learning model aided text dialogue and groups of students who were taught by conventional learning at IV grade Elementary School students of Gugus Budi Utomo academic year of 2017/2018. This research was a quasi experimental design with a non-equivalent post-test only control group design. The population of this research is all IV grade Elementary School students of Gugus Budi Utomo, amounting to 315 students. The sample was determined using group sample technique. The sample in this research is the students of IVB grade Elementary School students 6 Kesiman amounting to 31 students as experimental group and IV grade Elementary School students 14 Kesiman amounting to 38 students as control group.The instrument for collecting data is the scoring rubric. The data obtained were analyzed by t-test. The result of the analysis shows that there is a significant difference of competence of speaking skill in Indonesian between group of students who were taught by role playinglearning model aided text dialogue and groups of students who were taught by conventional learning at IV grade Elementary School students of Gugus Budi Utomo academic year of 2017/2018. This is evidenced by the result = 3,81 > = 2,00 at 5% significance level and dk = 67. The average score competence of speaking skill in Indonesian experimental group = 85,00 >= 76,45 control group. It can be concluded that there is influence of role playing learning model aided text dialogue to competence of speaking skill in Indonesian of IV grade Elementary School students of Gugus Budi Utomo academic year of 2017/2018